ANALISIS DAN PERANCANGAN SISTEM INFORMASI SURAT MENYURAT SEBAGAI USULAN PENGEMBANGAN APLIKASI YANG TELAH BERJALAN DI BAGIAN UMUM PEMKAB SITUBONDO - Imron Sodikin; Lukman Faqih Lidinillah (Jurnal Riset Teknik Komputer, 2025)
A correspondence information system in the General Affairs Division of the Situbondo Regency Government was previously available and used to assist in the management of incoming and outgoing mail, and disposition. However, the existing system still had several limitations, including in terms of feature completeness, ease of archive search, and communication of letter attachments. This condition resulted in the correspondence administration process not running optimally. This study aims to analyze the weaknesses of the existing information system and design a development proposal to better suit the agency's needs. The research method was carried out through observation, interviews, and analysis of the current system. The analysis results indicated that system development is needed, especially in aspects of attachment management, more detailed letter recording, and structured disposition tracking. Therefore, a proposal was designed to develop a web-based information system capable of supporting more effective and efficient letter management. With this development, the correspondence information system in the General Affairs Division of the Situbondo Regency Government is expected to improve employee performance, accelerate communication flows, and minimize administrative errors.